Marketing Strategies of Gift and Souvenir Shops in Canada and the United States: A Comparative Exploratory Study - Héroux, Lise; Church, Nancy J. (Téoros)

(untitled) (Université du Québec à Montréal, 2014)
The souvenir is an integral part of the travel experience and most tourists return home with souvenirs to preserve and commemorate such experiences. However, souvenirs and souvenir retailing is for the most part an untapped field of research. This research investigates the marketing strategies implemented by gift/souvenir shops and whether differences are found between Canada (Quebec and Ontario regions) and the United States (Vermont/New York region). The findings suggest that differences exist in the marketing strategies of gift and souvenir shops in these three regions. The marketing strategy ratings for product, price, promotion, and place were consistently higher for Ontario gift shops, followed by New York, and lowest for Quebec. The qualitative findings provide some insight into the specific variables that contribute to these differences. Gift and souvenir shop owners may benefit from identifying best practices that differentiate the Ontario stores and make their marketing strategy more appealing to visitors. This may provide useful guidelines for implementing changes to improve their marketing strategy.